The Effect of Discipline on Employees’ Work Performance on the E-warong KUBE PKH Program at Social Empowerment and Poor Management of the Sosial Service of Pekanbaru - surya dailiati; Sri roserdevi nasution (Jurnal Niara, 2020)
This research aims to find out the effect of work discipline on the performance of employees on E-warong KUBE PKH at social empowerment and Poor People’s Management of Pekanbaru’s Sosial Department. This research is a quantitative research with an associative approach. Operational definition includes indicators and Discipline Variable (X) namely attendance, obedience to work standards, high alertness, and athical work. Then the performance variable (Y) is productivity, service quality, responsiveness, responsibility, and accountability. This research has a population of 39 people from the Office of Social Services in Pekanbaru, the sampling teachnique using the census method is the overall retrieval of the existing population. Data collection techniques used was Observation, Questionnaire and Documentation. Measurement data used is the Likert Scale. The data analysis technique used is Simple regression.Conclusions based on data analysis and testing of the resulting hypothesis, namely the influence of Discipline on the Performance of Supervisors on the E-warong KUBE PKH in the field of social empowerment and poor handling of the Social Service of Pekanbaru City obtained the results of Y = 14,576 + 0,722x and Significant t results of 72%. Then based on the test results of the Guerdian of the E-warong KUBE PKH in the field of social empowerment and the managent of the poor, Pekanbaru social services were 55,4%.